2022
DOI: 10.3390/ijerph191610112
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care, Burnout, and Patient Safety: Way to Eliminate Avoidable Harm

Abstract: Patient safety has been a big theme in the area of global health, as represented by the resolution of the World Health Organization (WHO) on “Global action on patient safety” in 2019 and the recently published “Global Patient Safety Action Plan 2021–2030 [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…A 2022 systemic review on the wellbeing of GPs during the COVID-19 pandemic reported that numerous GPs suffered from reduced work satisfaction, anxiety, symptoms of depression or burnout, and physical symptoms during COVID-19 [35]. Poor wellbeing among those working in PC has been linked to patient safety issues [36,37].…”
Section: Main Findingsmentioning
confidence: 99%
“…A 2022 systemic review on the wellbeing of GPs during the COVID-19 pandemic reported that numerous GPs suffered from reduced work satisfaction, anxiety, symptoms of depression or burnout, and physical symptoms during COVID-19 [35]. Poor wellbeing among those working in PC has been linked to patient safety issues [36,37].…”
Section: Main Findingsmentioning
confidence: 99%
“…Fatigue has been defined as an overwhelming sense of tiredness and exhaustion, with a lack of energy and associated impaired physical and/or mental functioning [25]. Burnout, fatigue and poor wellbeing among healthcare professionals are associated with reduced performance and patient-safety outcomes [26][27][28][29][30], yet burnout among GPs is consistently high across the globe [26,27,[31][32][33][34][35][36]. Workload and job pressures are key contributors to burnout and fatigue [26,27,[31][32][33][34][35][36][37], with primary care workload increasing in recent years due to a mismatch between capacity and demand [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout, fatigue and poor wellbeing among healthcare professionals are associated with reduced performance and patient-safety outcomes [26][27][28][29][30], yet burnout among GPs is consistently high across the globe [26,27,[31][32][33][34][35][36]. Workload and job pressures are key contributors to burnout and fatigue [26,27,[31][32][33][34][35][36][37], with primary care workload increasing in recent years due to a mismatch between capacity and demand [38,39]. With primary care workload unlikely to reduce in the immediate future, it is important to consider other factors that can influence burnout and fatigue among GPs.…”
Section: Introductionmentioning
confidence: 99%